2017
DOI: 10.1002/jsfa.8179
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of carnosol, rosmarinic acid and thymol on the oxidative stability of soybean oil using a simplex centroid mixture design

Abstract: Results showed that bioactive compounds are effective in maintaining oxidative stability of soybean oil. However, the binary interaction of rosmarinic acid and thymol caused a reduction in antioxidant activity and oxidative stability of soybean oil. Optimum conditions for maximum antioxidant activity and oxidative stability were found to be an equal ternary mixture of carnosol, rosmarinic acid and thymol. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The ANOVA results for the responses are summarized in Table . It was reported that an F value greater than 4.64 or a P value less than 0.05 indicated that the regression equations were statistically significant . Hence the coefficients of linear, quadratic and special cubic were highly significant in this study.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…The ANOVA results for the responses are summarized in Table . It was reported that an F value greater than 4.64 or a P value less than 0.05 indicated that the regression equations were statistically significant . Hence the coefficients of linear, quadratic and special cubic were highly significant in this study.…”
Section: Resultsmentioning
confidence: 49%
“…The proportions of the granular ceramsite adsorbent were optimized by the SCMD method (Version 17.0, Minitab Inc., State College, PA, USA) to achieve superior adsorption capacity and mechanical strength for practical application. The SCMD could express the relationship between different variables and responses as well as optimize the component elements . In this study, four components with different functions, namely natural volcanic powder ( x 1 ), bentonite ( x 2 ), corn starch ( x 3 ) and aluminum sulfate ( x 4 ), were defined as independent variables and restricted by lower bound: x 1 ≥ 0.4, x 2 ≥ 0.2, x 3 ≥ 0.1, x 4 ≥ 0.1 and x 1 + x 2 + x 3 + x 4 = 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the food industry is moving towards replacing the application of synthetic by natural antioxidants, which are considered safer and healthier [4]. Several studies proposed natural alternatives to BHA (butylated hydroxyanisole) and BHT (butylated hydroxytoluene) for effectively improving the lipid stability of soybean oil [5][6][7][8][9][10][11][12][13][14][15]. Agro-food products, by-products and wastes are rich in bioactive compounds [16][17][18][19][20][21][22][23][24][25] thus contributing to the development of new functional ingredients and products [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Rosmarinic acid (RA), a water-soluble natural antioxidant, has also been used to avoid oxidation of target components [17]. CA and RA have been recognized as food additives [18] and are increasingly being used in the food, nutrition, health [19], and cosmetics industries [18].…”
Section: Introductionmentioning
confidence: 99%